Legal Certainty for Electric Vehicle Investors in Indonesia - Naja, Muhammad Hikam; Dawud, Abdul Hady; Prakoso, Bhim (GoAcademica Research & Publishing, 2023)
Problems related to climate change are currently a problem that is attracting a lot of attention in several countries. Many countries in the world want to develop the electric vehicle industry, including Indonesia. However, Indonesia also experiences many obstacles, one of which is that it needs electric vehicle investors. In an effort to overcome this, the government continues to make improvements, one of which is improving the law. Because it is understood that the law is one of the most important aspects of efforts to obtain investment. However, the issue is whether the legal regulations regarding electric vehicle investment in Indonesia have provided legal certainty to investors. The research method used is normative-legal with a statutory and conceptual approach. The results obtained from the research are related to the study of whether or not there are legal regulations for electric vehicle investment by investors.